On Some Identities and Symmetric Functions for Balancing Numbers - Ali Boussayoud (Journal of New Theory, 2018)
In this paper, we derivenew generating functions of the product of balancing numbers, Lucas balancingnumbers and the Chebychev polynomials of the second kind by making use ofuseful properties of the symmetric functions mentioned in the paper.